Facilitators and barriers for use of rotavirus vaccine amongst various stakeholders and its implications for Indian context - A systematic review - Aditi Apte; Sudipto Roy; Ashish Bavdekar; Sanjay Juvekar; Siddhivinayak Hirve (Taylor & Francis Group, 2018)
Background: We performed a systematic review to evaluate factors affecting uptake of rotavirus vaccine amongst physicians, parents and health system. Methods: We identified 15 studies that met the inclusion criteria from 790 screened studies published between Jan 2005 to Jan 2016. Results: Perceived severity of rotavirus disease, efficacy of vaccine and recommendation by health authorities positively influenced uptake of vaccine amongst health care providers. Routine and timely vaccination with routine vaccines and availability of rotavirus vaccine in public health programme facilitated uptake. Family income, parental education and employment status positively influenced the decision to vaccinate by parents. Concerns about safety, high cost, additional workload and logistic problems in acquiring vaccine stocks were perceived as barriers. Conclusion: Improved awareness regarding the rotavirus vaccination amongst public and scientific community and strengthening of public health system for better and timely immunisation coverage are important factors to maximize uptake of rotavirus vaccine in India.